2021
DOI: 10.1007/s10528-021-10115-1
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Adipogenic ceRNA Network Based on lncRNA Expression Profile of Adipogenic Differentiation of Human MSC Cells

Abstract: The Long non-coding RNA (lncRNA) expression profile data of ten samples including human Mesenchymal Stem Cell (MSC) adipogenic differentiation 0, 3, and 6 days from the GEO database, and then perform gene ID conversion, BLAST comparison, and annotation marking. Finally, group A (treatment group on day 3 of differentiation and control group on day 0 of differentiation) obtained a total of 1180 mRNA and 185 lncRNA; group B (treatment group on day 6 of differentiation and control group on day 0 of differentiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Huang et al established a ceRNA network and reported that some differentially expressed non-coding RNAs might be involved in the regulation of muscle traits. Liang et al [48] identified 216 ceRNAs, including 26 lncRNAs, 27 miRNAs, and 64 mRNAs, in human mesenchymal stem cell (MSC) adipose differentiation at 0, 3, and 6 d. The mRNAs in the ceRNA network were found to be mainly associated with glucose homeostasis and the response to insulin stimulation, as well as many lipid metabolism-related pathways, such as Ras, hypoxia-inducible factor-1 (HIF-1), PI3K-Akt, and insulin signaling. Chen et al constructed a ceRNA network using RNA-seq data and annotated potential candidate miRNAs and circRNAs involved in udder development in sheep, providing further insights into the influence of miRNAs and circRNAs on udder development in this species [49].…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al established a ceRNA network and reported that some differentially expressed non-coding RNAs might be involved in the regulation of muscle traits. Liang et al [48] identified 216 ceRNAs, including 26 lncRNAs, 27 miRNAs, and 64 mRNAs, in human mesenchymal stem cell (MSC) adipose differentiation at 0, 3, and 6 d. The mRNAs in the ceRNA network were found to be mainly associated with glucose homeostasis and the response to insulin stimulation, as well as many lipid metabolism-related pathways, such as Ras, hypoxia-inducible factor-1 (HIF-1), PI3K-Akt, and insulin signaling. Chen et al constructed a ceRNA network using RNA-seq data and annotated potential candidate miRNAs and circRNAs involved in udder development in sheep, providing further insights into the influence of miRNAs and circRNAs on udder development in this species [49].…”
Section: Discussionmentioning
confidence: 99%
“…For example, lncRNA H19 targets LCoR by interacting with the miR-188 sponge, thereby affecting the osteogenic and adipogenic differentiation process of mouse BMSCs. LncRNA ADNCR inhibits adipogenesis and differentiation by targeting miR-204 [ 40 ]. Therefore, potential ceRNA networks have been predicted for the above four central genes.…”
Section: Discussionmentioning
confidence: 99%